2017
DOI: 10.1016/j.virol.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The function of DNA binding protein nucleophosmin in AAV replication

Abstract: Adeno-associated viruses (AAV) contain minimal viral proteins necessary for their replication. During virus assembly, AAV acquire, inherently and submissively, various cellular proteins. Our previous studies identified the association of AAV vectors with the DNA binding protein nucleophosmin (NPM1). Nucleophosmin has been reported to enhance AAV infection by mobilizing AAV capsids into and out of the nucleolus, indicating the importance of NPM1 in the AAV life cycle; however the role of NPM1 in AAV production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
(94 reference statements)
0
14
0
Order By: Relevance
“…A recent study reported the presence of G4s in the AAV genome. The DNA binding protein nucleophosmin (NPM1), which is known to enhance AAV infectivity, directly interacts with G4s: 18 putative G4s were identified, located within the inverted terminal repeat region ( 86 ).…”
Section: G-quadruplexes In Viruses: Presence and Functionmentioning
confidence: 99%
“…A recent study reported the presence of G4s in the AAV genome. The DNA binding protein nucleophosmin (NPM1), which is known to enhance AAV infectivity, directly interacts with G4s: 18 putative G4s were identified, located within the inverted terminal repeat region ( 86 ).…”
Section: G-quadruplexes In Viruses: Presence and Functionmentioning
confidence: 99%
“…In RNA viruses, such as retroviruses, flaviviruses, and filoviruses, G4s present in the long terminal repeat (LTR), in the UTR, or in the coding region modulate gene expression and recombination [ 31 38 ]. In DNA viruses, G4s present in the genomes of adeno-associated virus and human herpesviruses regulate viral DNA replication [ 39 43 ], while G4s in the promoter region of hepatitis B virus (HBV) and in the mRNA of Epstein-Barr virus modulate transcription and translation [ 44 ] [ 45 , 46 ]. However, most of these studies aimed to understand the role of individual viral G4s, while genome-wide studies using the entire viral genomes are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In the dsDNA group, G4s were described in both Herpesviridae and Papillomaviridae families [12][13][14][15][16][17][18][19][20]. In ssDNA viruses, the presence of G4s was reported in the adeno-associated virus genome [21]. RNA G4s were described in the genomes of both ssRNA (+) (i.e.…”
mentioning
confidence: 99%